2017
DOI: 10.3926/jiem.1996
|View full text |Cite
|
Sign up to set email alerts
|

The application of the triple bottom line approach to sustainability assessment: The case study of the UK automotive supply chain

Abstract: Purpose: The objective of this paper is to assess the level of sustainability of the UK automotive supply chain considering simultaneously the three dimensions of sustainability (economic, social and environmental) representing the Triple Bottom Line (TBL) approach.Design/methodology/approach: The assessment of the automotive SC’ sustainability is based on the framework proposed by Salvado, Azevedo, Matias and Ferreira (2011) and uses the Simple Additive Weighting (SAW) method to aggregate economic, environmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
31
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(38 citation statements)
references
References 62 publications
0
31
0
Order By: Relevance
“…This positive image can positively influence the revenue of a companyfor the automotive industry, 5.7% of revenues can be attributed to the sustainability image (Biesalski & Company, 2014). The existing approaches that try to assess the impacts on the three dimensions of sustainability in the automotive industry target the company level (Jasiński et al, 2016;Azevedo & Barros, 2017;Fritz et al, 2018). The approach by Azevedo & Barros (2017) developed a tool that took data for assessing the impacts on the triple bottom line for UK based automotive manufacturers.…”
Section: Sustainability In the Automotive Sectormentioning
confidence: 99%
See 1 more Smart Citation
“…This positive image can positively influence the revenue of a companyfor the automotive industry, 5.7% of revenues can be attributed to the sustainability image (Biesalski & Company, 2014). The existing approaches that try to assess the impacts on the three dimensions of sustainability in the automotive industry target the company level (Jasiński et al, 2016;Azevedo & Barros, 2017;Fritz et al, 2018). The approach by Azevedo & Barros (2017) developed a tool that took data for assessing the impacts on the triple bottom line for UK based automotive manufacturers.…”
Section: Sustainability In the Automotive Sectormentioning
confidence: 99%
“…The existing approaches that try to assess the impacts on the three dimensions of sustainability in the automotive industry target the company level (Jasiński et al, 2016;Azevedo & Barros, 2017;Fritz et al, 2018). The approach by Azevedo & Barros (2017) developed a tool that took data for assessing the impacts on the triple bottom line for UK based automotive manufacturers. Jasiński et al (2016) selected a set of sustainability assessment criteria from the literature and in combination with the results of 24 interviews with automotive experts they suggested 26 midpoint and 9 end-point environmental, resource, social and economic impact categories.…”
Section: Sustainability In the Automotive Sectormentioning
confidence: 99%
“…Nevertheless, these studies have shown that companies use a wide range of KPI's to evaluate each one of the sustainability pillars, generating a long list of indicators that needs to be managed. This has led some authors to develop methodologies based on aggregating all the indicators into a unique index (Azevedo & Barros, 2017;Erol, Sencer & Sari, 2011;Pérez, Guerrero, González, Pérez & Caballero, 2013). For example, Azevedo and Barros (2017) have designed a composite index giving a different weight to each one of the sustainability dimensions.…”
Section: Introductionmentioning
confidence: 99%
“…This has led some authors to develop methodologies based on aggregating all the indicators into a unique index (Azevedo & Barros, 2017;Erol, Sencer & Sari, 2011;Pérez, Guerrero, González, Pérez & Caballero, 2013). For example, Azevedo and Barros (2017) have designed a composite index giving a different weight to each one of the sustainability dimensions. However, this kind of composite indicators might not be intuitive to practitioners due to their academic perspective.…”
Section: Introductionmentioning
confidence: 99%
“…The paper attempts to develop a theoretical framework explaining the complex interactions of variables in the dynamic environment of sustainable supply chain management by using the Total Interpretive Structural Modeling technique. The sustainability of the UK automotive supply chain is assessed by Azevedo and Barros [6]. The study is based on a proposed sustainability index for the automotive industry from the literature.…”
Section: Literature Reviewmentioning
confidence: 99%